The pharmaceutical applications of a biopolymer isolated from Trigonella foenum-graecum seeds: Focus on the freeze-dried matrix forming capacity - Sonia Iurian; Elena Dinte; Cristina Iuga; Cătălina Bogdan; Iuliana Spiridon; Lucian Barbu-Tudoran; Andreea Bodoki; Ioan Tomuţă; Sorin E. Leucuţa (Elsevier, 2017)
The aim of the present study was to evaluate the funtion of fenugreek seed mucilage (FSM) as potential matrix forming agent for orodispersible pharmaceutical lyophilisates. The FSM was isolated and characterized. FSM colloidal dispersions were prepared and the rheological evaluation was performed. Oral lyophilisates (OLs) with different FSM concentrations, containing meloxicam as model drug were prepared by freeze drying method. The OLs were characterized and compared to gelatin containing tablets, prepared under the same conditions.The FSM dispersions revealed shear thinning flow type. Based on colloidal dispersions' rheological properties, five FSM concentrations were taken forward to the lyophilization step. Completely dry and elegant tablets were obtained. Texture analysis indicated highly porous structures, confirmed by SEM analysis, which explain the fast disintegration properties. All the prepared tablets disintegrated in less than 47 s. The disintegration process was prolonged by the increase in FSM content, due to the high viscosity the polymer creates in aqueous media. FSM tablets presented longer disintegration times, as compared to gelatin tablets, but also higher crushing strength. Considering the fast disintegration and the high crushing strength, FSM is a good candidate as matrix forming agent for fast disintegrating dosage forms or other freeze-dried preparations. Keywords: Meloxicam, Oral lyophilisates, Matrix forming agent, Galactomannan, Lyophilization